2021
DOI: 10.1108/ijph-08-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to health and social services for older prisoners transitioning to community

Abstract: Purpose When properly designed and implemented, prison-to-community transition programs targeting older prisoners could potentially save resources, reduce reoffending rates and contribute to improved public protection and safety. However, older prisoners transitioning to community are often neglected and overlooked, and thus, interventions targeted to address their needs are limited. The purpose of this study was to identify barriers and enablers to health and social services for older prisoners transitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…Whilst the motivation for improving digital literacy is present, the opportunities to prepare older people for release via digital literacy improvement, at least in Australia, appear underutilized. This aligns with the consistent evidence regarding a general lack of release planning practices (Hagos et al, 2021). According to this study, this may be because digital literacy for day-to-day life tasks is not considered a 'criminogenic' issue, i.e.…”
Section: Key Findings and Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…Whilst the motivation for improving digital literacy is present, the opportunities to prepare older people for release via digital literacy improvement, at least in Australia, appear underutilized. This aligns with the consistent evidence regarding a general lack of release planning practices (Hagos et al, 2021). According to this study, this may be because digital literacy for day-to-day life tasks is not considered a 'criminogenic' issue, i.e.…”
Section: Key Findings and Implicationssupporting
confidence: 88%
“…For example, Lares and Montgomery (2020) identified "Technology challenges" as a subtheme in their qualitative study of N=19 older people who had left prison. In another qualitative study by Hagos et al (2021), Australian correctional staff identified lack of digital literacy as a key barrier for health and social service access in older people leaving prison. One cross-sectional survey of N=255 adult prisoners in Finland regarding their use of digital health care and social welfare services found that age was an All rights reserved.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…In Australia, a growing body of literature recognises the rapid ageing of the prisoner population with qualitative studies, economic analyses, examination of offending data and commentaries conducted by academics and various government agencies all acknowledging this issue (Australian Institute of Health and Welfare, 2019; Ginnivan et al, 2021;Hagos et al, 2021;Howard & Corben, 2019;Hwang et al, 2021;Inspector of Custodial Services NSW, 2015; Office of the Inspector of Custodial Services WA, 2021;Simpson et al, 2017;Trotter & Baidawi, 2015). Whilst mostly focused on prisoner population ageing or prisoner health management in general, all emphasise the importance of appropriate post-release support for older prison leavers.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst mostly focused on prisoner population ageing or prisoner health management in general, all emphasise the importance of appropriate post-release support for older prison leavers. One qualitative study with correctional staff (N=32) in Australia specifically focused on investigating the specific barriers and enablers to post-release reintegration in older prison leavers, and identified that the challenges exist at not only the personal, but also the social, economic and organisational levels (Hagos, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation